Authority of Customary Village Heads in Bali from a Positive Legal Perspective at the Local Level - Dewa Krisna Prasada; Kadek Ray Sulyantha; Ida Bagus Arya Lawa Manuaba; I Putu Duta Krisna Dvaipayana (Indonesian Journal of Law and Islamic Law (IJLIL), 2024)
Customary villages are an integral component of a nation, especially Indonesia. The customary village in the Province of Bali is a village that preserves cultural traditions and retains the traditional village governance system. The heads of customary villages in Bali are granted local authority under Law Number 6 of 2014 and Bali Provincial Regulation Number 4 of 2019, which pertain to customary villages. Nevertheless, a legal problem arises due to the lack of clarity regarding the authority of local-scale legislation mentioned above. This leads to overlapping and discriminatory actions by traditional village leaders in Bali. This study examines the limits of local-scale jurisdiction in the autonomy of customary village heads in Bali from a legal standpoint. This study employs a normative research methodology, utilizing a statute approach and analyzing legal concepts. The sample in this study uses primary legal materials, specifically laws and regulations, from Indonesia. The methodology employed in this work involves using prescriptive legal analysis approaches. This study finds that the jurisdiction of customary village heads in Bali is constrained by the notions of authority and local context. The authority of the head of the customary village encompasses traditional, cultural, religious, and economic activities, all confined to the territory or land controlled by the customary village. Contribution of this research  to enhance the comprehension of indigenous village chiefs in Bali on the local jurisdiction of indigenous leaders, so preventing legal discrepancies that may result in overlapping authority and prejudice within the community.